Rendimiento de morteros producidos con la incorporación de ceniza de bagazo de caña de azúcar - Macedo, Pamela Camargo [UNESP]; Pereira, Adriana Maria [UNESP]; Akasaki, Jorge Luis [UNESP]; Fioriti, Cesar Fabiano [UNESP]; Payá, Jordi; Melges, José Luiz Pinheiro [UNESP] (My University, 2014)
This paper presents the technical feasibility of using ash in mortars, from burning sugarcane bagasse, to generate power as a mineral admixture. The sugarcane bagasse ash (SCBA) underwent chemical characterization and x-ray diffraction tests. The milling of the material was studied, together with the composition of the mortars containing the SCBA at 3%, 5%, 8% and 10% ratios by weight, as partial replacement of fine aggregates. The mechanical properties were studied by compressive and diametral tensile strength tests. Some properties related to the durability of the material were also studied, such as drying shrinkage, capillary absorption and accelerated reactivity. The work was performed using low pozzolanic activity SCBA. However, the results indicate that it is possible to use SCBA as partial replacement of fine aggregates in the production of mortars.
Performance of mortars produced with the incorporation of sugar cane bagasse ash
Keywords: Mineral admixture; Mortar; Sugarcane bagasse ash